Caracterização dos Mármores de Estremoz no contexto dos mármores da Antiguidade Clássica da Zona de Ossa-Morena - Moreira, Noel (2020)
This work presents, in a non-exhaustive way, the main geological features of the Estremoz Anticline marbles (historically known as Estremoz Marbles). This geological characterization comprises the description of the main features of these marbles from their origin and geodynamic evolution, but whenever possible it will seek to make a connection with the archaeological sciences. The Estremoz Marbles have been exploited at least since Classical Antiquity. It is known that they had widespread use in many places of the Roman Empire, for their petrographic characteristics (both textural and mineralogical), their chemical composition and isotopic signature, which are intrinsic to their nature and geodynamic evolution, allowing a very reliable identification of their geographical origin. However, this approach of their origin must also be a comparative view with other marbles used in the same time period and also located in the same tectono-stratigraphic zone (Ossa-Morena Zone). All the marbles from the Ossa-Morena Zone experienced a similar geological evolution during the Palaeozoic (541-252 million years), although each one of these marbles has its own evolutionary specificities that allow the differentiation from other classic marbles, namely the marbles with Mediterranean origin. The geological features of each of those marbles control both the methods of extraction and their uses. In summary, this multidisciplinary work correlates geomorphology, composition and structural arrangement, technological properties, extraction, processing and application techniques, and the geographic dissemination of the Estremoz Marbles in Classical Antiquity, also showing how these factors are strongly conditioned by geology and geodynamic evolution, telling us the geological history of the Estremoz Marbles.